Exploring the Effectiveness of Digital Technology in Nepalese Higher Education : An Institutional Ethnography Research Design (Pragya Darshan प्रज्ञा दर्शन, 2025)
Digital technology seems at the mandatory component of all educational institutions like schools, colleges and universities as well. In Nepal , very few universities had started using digital technology during covid period without proper infrasturature and training . Researcher felt to explore how effectively conduct teaching at  higher education with digital technology . However ,this study aims at exploring the effectiveness of digital technology at higher education in Nepal. It was guided by qualitative research followed by institutional ethnographic research design. Altogether five teachers, five students and two IT experts were chosen as a sample from the Central Department of Education, Tribhuvan University, Kirtipur, by following a purposive sampling technique. Similarly, qualitative information was garnered  by using in-depth interviews and document analysis to get a deeper understanding of the topic being researched. Furthermore, collected data were edited, transcribed, coded and thematized to gain meaningful results and conclusions by considering the objectives of the study. The results have revealed that all respondents in the educational process have a positive perception of using digital technologies in higher educational institutions.  Sufficient infrastructure and intensive teacher training should be provided to make the confident teachers and effective instruction via   ICT in higher education . The demand on advancement of technology has increased day bye day globally . It has made the additional way to provide quality education easily than before . However , this findings highlight and capture the effectiveness of digital technology for fulfillment of sustainable development goals but also remains the same problem  for a long time about  the appropriate infrastructure , teacher training and need to develop students’ efficacy .